Associative learning in a mouse model of Alzheimer’s disease - Armstrong, Paul (2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease defined by severe memory loss and the accumulation of amyloid plaques and neurofibrillary tangles in the brain. The experiments presented in this thesis examined cognitive performance in a well-‐characterised mouse model of AD, the APPswe/PS1dE9 (TG) mouse, at 4-‐5 months old prior to extensive amyloid plaque deposition. The experiments employed were associative learning tasks, which are not often used to measure cognitive performance in classical neuroscience research into neurodegenerative disease.